Administrative sanctions as a manifestation of state coercion - Stankiewicz, Rafał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Administrative sanctions are an integral part of the exercise of state power, which consists in using coercion. They are designed as consequences for violating legal regulations, derived from generally applicable provisions of administrative law. This article discusses the issue and the types of administrative sanctions under Polish law
Keywords: administrative sanctions; state coercion; administrative coercion; administrative law